Treatment of venous thromboembolism with rivaroxaban in relation to body weight - Nisio, Marcello Di; Vedovati, Maria C.; Riera-Mestre, Antoni; Prins, Martin H.; Mueller, Katharina; Cohen, Alexander T.; Wells, Philip S.; Beyer-Westendorf, Jan; Prandoni, Paolo; Bounameaux, Henri; Kubitza, Dagmar; Schneider, Jonas; Pisters, Ron; Fedacko, Jan; Fontes-Carvalho, Ricardo; Lensing, Anthonie W. A. (Thrombosis and Haemostasis, 2016)
The pharmacokinetics of oral rivaroxaban are highly predictable and only affected to a limited extent by bodyweight; therefore, dose adjustments for bodyweight are not required. However, this raises concerns among physicians for potential under- or overdosing. This substudy of the randomised EINSTEIN DVT and EINSTEIN PE trials, which compared rivaroxaban with enoxaparin/vitamin K antagonist (VKA) therapy, aimed to determine the incidence of major bleeding in patients with a low bodyweight and recurrent venous thromboembolism (VTE) in patients with a high bodyweight during rivaroxaban or enoxaparin/VKA therapy. More than 8,000 patients with objectively diagnosed deepvein thrombosis or pulmonary embolism were included. Adjusted hazard ratios for recurrent VTE and bleeding were calculated using the Cox proportional hazards model. Analyses were performed for both the first 21 days of treatment and the whole treatment period. For rivaroxaban recipients, there was no association between bodyweight or body mass index (BMI) and risk of recurrent VTE (ptrend=0.87 and 0.62, respectively), major bleeding (ptrend=0.24 and 0.36, respectively) or clinically relevant bleeding (ptrend=0.17 and 0.63, respectively). Major bleeding events were numerically lower in rivaroxaban patients across all bodyweight and BMI categories. Hazard ratios for rivaroxaban vs enoxaparin/VKA were similar in all bodyweight and BMI categories, both during the first 21 days and the whole treatment period. The fixed-dose rivaroxaban regimen is not associated with an increased risk of major bleeding or recurrent VTE in patients with either a low or high bodyweight. A high BMI was not associated with an increased risk of recurrent VTE during anticoagulation.Note: This study was presented at the 25th Congress of the International Society on Thrombosis and Haemostasis; June, 2015, Toronto, Canada. Trial registration: EINSTEIN DVT (NCT00440193), EINSTEIN PE (NCT00439777).
Keywords: Body mass index; bodyweight; rivaroxaban; venous thromboembolism